Migrasi Batak Toba ke Medan Sebelum Era Otonomi: Antara Alasan Ekonomi dan Pendidikan - Elvis Fresly Purba; Lastri Lastri (Ideas Publishing, 2023)
Migration of the Toba Batak people to Medan began at the end of the 19th century, but the flow of migration up to independence was relatively slow. However, after independence it increased so that in 1981, 1988 and 2000 it became the second order. Of course, the reason for the transfer can be different in terms of push factors and pull factors. The purpose of this research is to find out the causal factors why the Toba Batak people entered Medan since several decades ago until the era of autonomy. The research was conducted in five districts from March to August 2022. Sampling was carried out by accidental sampling and snowball sampling with a total of 200 families as respondents. All respondents were born in North Tapanuli Regency who came to Medan in the 1950-2000 period. The results of the study show that the two main factors causing the displacement are educational reasons in the first place and economic reasons in the second place. In contrast, in previous studies, economic reasons were in first place while educational reasons were in second place. The conclusion from this research is that in the era of autonomy and the era of tourism development, the potential for Lake Toba and the surrounding area to become a very valuable asset to realize the expectations of the central government, namely to make Lake Toba a national and foreign tourist destination.